2020
DOI: 10.1088/1741-4326/abc318
|View full text |Cite
|
Sign up to set email alerts
|

Runaway electron mitigation with supersonic molecular beam injection (SMBI) in ADITYA-U tokamak

Abstract: The generation and subsequent loss of runaway electrons (REs) during the operation sequence in a tokamak is a potent threat to the plasma-facing components and the interface of actively cooled parts. Control and mitigation of REs are of prime importance to the safe operation and machine health of a fusion device. A supersonic molecular beam injection (SMBI) system has been installed in the ADITYA-U tokamak to explore the effects of the high Mach number molecular beam on the REs and ways to mitigate the REs. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…However, there are some discharges where the REs are affected less and HXR bursts are not reduced appreciably after the SMBI pulse. There is a strong correlation observed between mode rotation frequency of tearing modes and RE reduction [30]. With the sharp reduction in mode rotation frequency, the HXR burst is substantially reduced.…”
Section: Res Mitigation By Smbi In Aditya-umentioning
confidence: 87%
“…However, there are some discharges where the REs are affected less and HXR bursts are not reduced appreciably after the SMBI pulse. There is a strong correlation observed between mode rotation frequency of tearing modes and RE reduction [30]. With the sharp reduction in mode rotation frequency, the HXR burst is substantially reduced.…”
Section: Res Mitigation By Smbi In Aditya-umentioning
confidence: 87%
“…The radial electric field has been estimated from the measurement of poloidal and toroidal rotation velocities over the plasma radius [19]. Furthermore, experiments on fuelling with supersonic molecular beam injection for RE mitigation have also been carried out in ADITYA-U [20].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of RE beam stability, control and mitigation were also reported from the COMPASS [102] and ADITYA-U [103] devices utilizing RE beams in ohmic flat-top plasmas. Focussing on stability and control of the RE beam, the COMPASS team reported that while vertical position control did not present major challenges, even at high values of elongation, maintaining radial position was more problematic.…”
Section: Disruption Prevention Avoidance and Mitigationmentioning
confidence: 99%